2022
DOI: 10.1093/jbcr/irab250
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Preparation, Mechanism, and Clinical Application of Nanofat

Abstract: Autologous adipose tissue is an ideal soft tissue filling material in theory, which has the advantages of easy access, comprehensive source, and high biocompatibility and is now widely used in clinical practice. Based on the above benefits of autologous fat, autologous fat grafting is an essential technique in plastic surgery. Conventional macrofat is used to improve structural changes after soft tissue damage or loss caused by various causes such as disease, trauma, or aging. Due to the large diameter of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Coincident with this, noninvasive techniques have trended towards regenerative medicine, focusing on the efficacy of autologous stem cell transfer in healing and tissue repair. Autologous platelet and fat concentrates are promising therapeutic agents in regenerative medicine since they are a great source of cytokines, growth factors and other biologically active substances [9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coincident with this, noninvasive techniques have trended towards regenerative medicine, focusing on the efficacy of autologous stem cell transfer in healing and tissue repair. Autologous platelet and fat concentrates are promising therapeutic agents in regenerative medicine since they are a great source of cytokines, growth factors and other biologically active substances [9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated excellent clinical evidence of the role of fat cells as well as adipocyte-derived stem cells in stimulating skin rejuvenation. It has previously shown efficacy for burn scars, fibrosis, pain and radiation damage [15][16][17][18] . PRP and its effects on facial rejuvenation have been described.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanofat is a new technique that has recently gained popularity in cosmetic surgery. Studies have shown that nanofat contains no viable adipocytes but is more abundant in stromal vascular fraction cells and adipose-derived stem cells [ 14 ], thereby enhancing skin quality and promoting tissue regeneration. It is also liquid, in comparison to other types of fat, due to the absence of adipocytes, which means that it lacks a volumizing effect [ 15 ].…”
Section: Introductionmentioning
confidence: 99%